Integration Telemental Health to Reach Out Patients at Community Mental Health Services: A Systematic Review - Rian Priambodo; Rizki Fitryasari; RR Dian Tristiana; Firnanda Erindia; Wimar Anugrah Romadhon (STIKes Patria Husada Blitar, 2024)
Low- and middle-income countries (LMICs) need to digitize mental health services to address disparities and improve access to healthcare. This study systematically reviewed the digitalization of integration mental health services that can reach interactions between service providers and recipients with media such as telemental health and mobile health. A literature search was conducted in March 2023. Randomized controlled trial (RCT) data were used from available studies. RCT data sources were obtained from internationally reputable journal articles with the theme of telehealth. The literature used was obtained from the databases Scopus, Web of Science, and PubMed. Integration digitalized mental healthcare system under the auspices of the Ministry of Health that reach-nationally, official psychiatrists and other professional mental healthcare that provides mental healthcare support to areas lacking specialists consisting crisis and emergency, stable conditions, as well as the process of counseling and follow-up therapy with telemental health and mobile health media. Telemental health plays a major role in mental health services and modality therapy that can be accessed effectively and efficiently, especially for mental patients in remote areas who experience barriers to attending in person.